ARSITEKTUR DAN DESAIN KOTA HIBRIDA PADA KANTOR POS DAN ALUN-ALUN DI MEDAN - Siti Rukayah; Sudarmawan Juwono (Diponegoro University, 2018)
The traditional citi center in Java has a composition of the square. The philosophy of the city is as the center of the country which is lead by the king. The regency cities in Java adopt this concept with the similar composition. In the Dutch colonial era of the 18-19th century, the postweg line is connected the regency cities in Java, with the post office located near the city center. Medan in Sumatra becomes the case to eximen how the architectural concept of the post office and Merdeka field (resembling the square in Java) as the work of the Dutch government at that time. The purpose of this study is to uncover the concept of the post office located at the zero point of the city and Merdeka Field as the square in the city center. By using the historical and grounded research, it is found that Medan is a unique city. The hybrid architectural design of the post office classifies the shape of the old city center in Medan, which has the hybrid concept which has the philosophy of meeting various cultures. The Java and Dutch concept for urban design is affected by Java, Malay, and Chinese for building design.